Viral CNS infections: role of glial pattern recognition receptors in neuroinflammation - Furr, Samantha; Marriott, Ian (Frontiers in Microbiology, 2012)
Viruses are the major causative agents of central nervous system (CNS) infection worldwide. RNA and DNA viruses trigger broad activation of glial cells including microglia and astrocytes, eliciting the release of an array of mediators that can promote innate and adaptive immune responses. Such responses can limit viral replication and dissemination leading to infection resolution. However, a defining feature of viral CNS infection is the rapid onset of severe neuroinflammation and overzealous glial responses are associated with significant neurological damage or even death. The mechanisms by which microglia and astrocytes perceive neurotropic RNA and DNA viruses are only now becoming apparent with the discovery of a variety of cell surface and cytosolic molecules that serve as sensors for viral components. In this review we discuss the role played by members of the Toll-like family of pattern recognition receptors in the inflammatory responses of glial cells to the principle causative agents of viral encephalitis. Importantly, we also describe the evidence for the involvement of a number of newly described intracellular pattern recognition receptors, including retinoic acid-inducible gene I and DNA-dependent activator of IFN regulatory factors, that are thought to function as intracellular sensors of RNA and DNA viruses, respectively. Finally, we explore the possibility that cross-talk exists between these disparate viral sensors and their signaling pathways, and describe how glial cytosolic and cell surface/endosomal pattern recognition receptors could act in a cooperative manner to promote the fulminant inflammation associated with acute neurotropic viral infection.